Identifying the effects of health insurance coverage on health care use when coverage is misreported and endogenous - Ha Trong Nguyen; Huong Thu Le; Christopher Blyth; Luke Connelly; Francis Mitrou (Global Labor Organization (GLO), 2024)
The examination of the causal impact of health insurance coverage on healthcare utilisation is a critical endeavour in both academic research and policy formulation. However, this endeavour faces challenges, notably the endogenous selection into coverage and prevalent misreporting of coverage status. This study pioneers an investigation into the effects of private health insurance (PHI) coverage on healthcare utilisation, considering the intricacies of misreporting and endogeneity. To address misreporting, we analyse linked survey and administrative data with a precise coverage indicator. For endogeneity, we employ four established methodologies, including an instrumental variable approach leveraging an age-based policy discontinuity to construct an instrument. Our findings unveil that individuals with PHI coverage tend to access healthcare services more frequently, particularly primary care visits and specialist consultations. Nonetheless, the magnitude and statistical significance of these effects exhibit variability across different healthcare services and methodological approaches. Additionally, we discern notable disparities in the magnitude of PHI estimates between survey-based and administrative PHI indicators, with varying discrepancies across services and methodologies. Notably, our preferred specification underscores that utilising a self-reported PHI indicator with a 10% misreporting rate would result in a substantial overestimation of PHI's impact on the two most commonly utilised healthcare services.
Keywords: C18; C81; C83; H31; I12; I13; I18; 330; Health Insurance; Measurement Error; Health Care Demand; Australia